2021
DOI: 10.1002/jocc.12194
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ+ Structural Stigma and College Counseling Center Website Friendliness

Abstract: We examined whether the “friendliness” of college counseling center websites to students with lesbian, gay, bisexual, transgender, and queer, plus other identities (LGBTQ+) varied by state‐level structural policies on hate crime, employment nondiscrimination, and religious exemption. Results from our analyses of variance showed that website friendliness was significantly higher in states that offered hate‐crime and employment nondiscrimination protections to LGBTQ+ individuals. Our findings highlight the need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Likewise, Hollinsaid et al (2022) documented substantially lower rates of mental health providers who specialize in providing services to transgender youth in states with more transphobic laws/policies while controlling for other state-level factors, such as political and religious conservatism. Similar studies have also identified a dearth of genderaffirming assessment materials (e.g., inclusive online intake forms; Holt et al, 2019Holt et al, , 2021, fewer referrals for gender-affirming services for transgender youth (Indremo et al, 2022), and less affirming services for sexual minority and transgender young people (Campbell & Mena, 2021) in places with high levels of structural stigma. In sum, research suggests that stigma increases stigmatized youth's need for mental health treatment by worsening their mental health, makes it harder for stigmatized youth to benefit from treatment, and finally, makes it harder for them to access appropriate treatment.…”
Section: Structural Stigma and Mental Health Treatment Efficacy And A...mentioning
confidence: 84%
“…Likewise, Hollinsaid et al (2022) documented substantially lower rates of mental health providers who specialize in providing services to transgender youth in states with more transphobic laws/policies while controlling for other state-level factors, such as political and religious conservatism. Similar studies have also identified a dearth of genderaffirming assessment materials (e.g., inclusive online intake forms; Holt et al, 2019Holt et al, , 2021, fewer referrals for gender-affirming services for transgender youth (Indremo et al, 2022), and less affirming services for sexual minority and transgender young people (Campbell & Mena, 2021) in places with high levels of structural stigma. In sum, research suggests that stigma increases stigmatized youth's need for mental health treatment by worsening their mental health, makes it harder for stigmatized youth to benefit from treatment, and finally, makes it harder for them to access appropriate treatment.…”
Section: Structural Stigma and Mental Health Treatment Efficacy And A...mentioning
confidence: 84%
“…Likewise, Hollinsaid et al (2022) documented substantially lower rates of mental health providers who specialize in providing services to transgender youth in states with more transphobic laws/policies while controlling for other state-level factors, such as political and religious conservatism. Similar studies have also identified a dearth of genderaffirming assessment materials (e.g., inclusive online intake forms; Holt et al, 2019Holt et al, , 2021, fewer referrals for gender-affirming services for transgender youth (Indremo et al, 2022), and less affirming services for sexual minority and transgender young people (Campbell & Mena, 2021) in places with high levels of structural stigma. In sum, research suggests that stigma increases stigmatized youth's need for mental health treatment by worsening their mental health, makes it harder for stigmatized youth to benefit from treatment, and finally, makes it harder for them to access appropriate treatment.…”
Section: Structural Stigma and Mental Health Treatment Efficacy And A...mentioning
confidence: 84%
“…For example, there is evidence that resilience (i.e., the ability to bounce back in stressful situations) and identity pride may buffer SGM students from the effects of heterosexism, cisgenderism, and harassment on college campuses (Woodford, Weber, et al, 2018) While expanding access to mental health for SGM students appears to be part of the answer, increasing access may not be sufficient by itself. In their examination of state-level structural policies as predictors of college counseling center website SGM friendliness, Campbell and Mena (2021) found that colleges in states with hate-crime and employment non-discrimination protections for individuals identifying as an SGM had friendlier websites as indicated by factors such as mentions of SGM specific resources, services, or information and direct or indirect support statements. Thus, students in states or regions in which they may be more likely to experience heterosexism or harassment may also be the states in which college counseling centers are least explicitly welcoming to SGM students.…”
Section: Discussionmentioning
confidence: 99%